2015
DOI: 10.3390/s150202964
|View full text |Cite
|
Sign up to set email alerts
|

A Data Fusion Method in Wireless Sensor Networks

Abstract: The success of a Wireless Sensor Network (WSN) deployment strongly depends on the quality of service (QoS) it provides regarding issues such as data accuracy, data aggregation delays and network lifetime maximisation. This is especially challenging in data fusion mechanisms, where a small fraction of low quality data in the fusion input may negatively impact the overall fusion result. In this paper, we present a fuzzy-based data fusion approach for WSN with the aim of increasing the QoS whilst reducing the ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 32 publications
(31 reference statements)
0
59
0
Order By: Relevance
“…In addition, important research can be found in adopting FL in aggregation mechanisms. In [29], a fuzzy-based data fusion approach for WSNs is proposed. The model aims to increase the QoS while reducing the energy consumption of nodes.…”
Section: E Information Aggregation Under Uncertaintymentioning
confidence: 99%
“…In addition, important research can be found in adopting FL in aggregation mechanisms. In [29], a fuzzy-based data fusion approach for WSNs is proposed. The model aims to increase the QoS while reducing the energy consumption of nodes.…”
Section: E Information Aggregation Under Uncertaintymentioning
confidence: 99%
“…Demin et al [58] introduce an algorithm for maximum data collection rate in rechargeable wireless sensor networks with multiple sinks. In [59], the authors present a fuzzy-based data fusion approach for increasing the QoS whilst improving the data collection rate and reducing the energy consumption of the sensor network.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, this technique needs to be applicable in different application environments and more importantly minimizes the aforementioned delay factor in WSNs. In the literature, data fusion and aggregation mechanisms are centered on how to efficaciously use the on‐board batteries of sensor nodes to enhance the WSNs' lifetime . These approaches utilize different mechanisms proposed in the literature such as fuzzy set theory, sampling techniques, theory of probability, a hybrid of fuzzy set and probability, and evidence theory proposed by Dempster‐Shafer .…”
Section: Introductionmentioning
confidence: 99%